Remote imaging by nanosecond terahertz spectrometer with standoff detector - Huang, Zhiming; Andreev, Yury M. 1946-; Kokh, Konstantin A.; Lanskii, Grigory V.; Potekaev, Aleksandr I. 1951-; Huang, Jingguo; Svetlichnyi, Valerii A. (Russian physics journal)
Creation and application of the remote imaging spectrometer based on high power nanosecond terahertz source with standoff detector is reported. 2D transmission images of metal objects hided in nonconductive (dielectric) materials were recorded. Reflection images of metal objects mounted on silicon wafers are recorded with simultaneous determination of the wafer parameters (thickness/material).